2020
DOI: 10.1038/s41598-020-74907-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative fluids and complications after pancreatoduodenectomy within an enhanced recovery pathway

Abstract: Optimized fluid management is a key component of enhanced recovery (ERAS) pathways. Implementation is challenging for pancreatoduodenectomy (PD) and clear guidance is missing in the respective protocol. The aim of this retrospective study was to evaluate the influence of perioperative intravenous (IV) fluid administration on postoperative complications. 164 consecutive patients undergoing PD within ERAS between October 2012 and June 2017 were included. Perioperative IV fluid and morbidity (Clavien classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The secondary outcome of interest, a clinically relevant postoperative pancreatic fistula (Grade B or C), was observed in 11.9% of the cohort, consistent with other reports. [ 6 , 9 , 10 , 15 , 37 ]. In those studies, increased intraoperative [ 9 ] or post-operative [ 15 ] fluid balance was associated with a CR-POPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary outcome of interest, a clinically relevant postoperative pancreatic fistula (Grade B or C), was observed in 11.9% of the cohort, consistent with other reports. [ 6 , 9 , 10 , 15 , 37 ]. In those studies, increased intraoperative [ 9 ] or post-operative [ 15 ] fluid balance was associated with a CR-POPF.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, increased intraoperative [ 9 ] or post-operative [ 15 ] fluid balance was associated with a CR-POPF. Others showed no multivariate association between volume status and Grade B or C POPF [ 6 , 11 , 12 , 37 ]. Our multivariate observations align with the findings that indicate no association between volume status and Grade B or C POPF.…”
Section: Discussionmentioning
confidence: 99%
“…According to Gottin et al [ 45 ], significantly fewer postoperative complications (eg, postoperative fistula, abdominal collection, and hemorrhage) were found in the restrictive fluid therapy group (≤4 ml/kg/h) than in patients who had received liberal fluid therapy (≥12 ml/kg/h). Gilgien et al [ 46 ] also concluded that patients who received ≥4400 ml intravenous fluids during the first 24 h after surgery had more complications, especially pulmonary complications. Liberal fluid therapy may also lead to an increase in postoperative pancreatic fistula (POFF) formation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…For pain control, pre-induction single dose of IV dexmedetomidine 11 paracetamol 12 truncal analgesic blocks, specifically transversus abdominus plane and quadratus lumborum blocks, 13 are advocated. They recommend against excess fluid administration, 14 although there is no evidence to support the use of restricted fluid regimens such as goal-directed fluid therapy. 10 As with the general surgical population, avoiding nasogastric tube placement in pancreatic transplant recipients resulted in a decreased hospital length of stay without resulting in other complications.…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 99%